Acontecimiento y sentido - Viola, Federico Ignacio (ARFIL y UNL, 2018)
In the present paper it is shown, following Levinas, that Ethics, understood as an intersubjective relation among completely separate subjects, sets itself up starting from concrete events that determine man's historical existence, but these are invested with the peculiarity of being events which escape the ontological order. Rather, they send to somewhere beyond, outside ontology, signifying above all in an ethical fashion, i.e., in a way other than being.